Elevated transcription of the gene QSOX1 encoding quiescin Q6 sulfhydryl oxidase 1 in breast cancer. - Mikhail Soloviev; Michelle P Esteves; Fakhria Amiri; Mark R Crompton; Christopher C Rider (PLoS ONE, 2013)
The q arm of chromosome 1 is frequently amplified at the gene level in breast cancer. Since the significance of this is unclear we investigated whether 1q genes are overexpressed in this disease. The cDNA levels of 1q-located genes were analysed in a search for overexpressed genes. 26 genes mapping to the 1q arm show highly significant (P≤0.01) overexpression of transcripts in breast cancer compared to normal breast tissue. Amongst those showing the highest levels of overexpression in both expressed sequence tag (EST) and serial analysis of gene expression (SAGE) databases was enzyme quiescin Q6 sulfhydryl oxidase 1 (QSOX1). We investigated QSOX1 cDNA derived from T47D breast carcinoma cells by RT-PCR and 3'-RACE PCR and identified a novel extended form of QSOX1 transcript, containing a long 3'UTR, nearly double the size of the previously reported QSOX1 cDNA, and confirmed its 3' end nucleotide sequence using RACE-PCR. We also used quantitative real-time PCR to analyse a panel of cDNAs derived from 50 clinically-graded normal and malignant breast tissue samples for the expression of QSOX1 mRNAs. QSOX1 transcription was elevated in an increasing proportion in the grade 2 and grade 3 tumours (graded according to the Nottingham prognostic index), with 10 of the 15 grade 3 tumours (67%) examined exceeding the normal range. There was a significant correlation between relative transcript level and clinical grade (P≤0.01) for all qPCR primer sets tested. QSOX1 mRNA levels, based on SAGE expression data, did not correlate with either Estrogen Receptor (ER) or Epidermal Growth Factor Receptor 2 (ErbB-2 or HER2/neu) expression. Our data indicate that QSOX1 is a potential new prognostic marker which may prove of use in the staging of breast tumours and the stratification of breast cancer patients.